Neil Kinnock saving the labour party? - Hickson, Kevin 1974- (Routledge, Taylor & Francis Group, 2022)
"The book reappraises Neil Kinnock's policies, impact, legacy, and leadership of the Labour Party thirty years on from his defeat in the 1992 General Election. It offers comprehensively fresh perspectives and some first-hand accounts - some friendly, others more critical - from leading academics, journalists, politicians, and advisors on various aspects of ideas, policy, elections, and party management, including an interview with the man himself as he looks back on his experiences. This timely book will resonate widely with the current challenges to Labour's leadership and the enduring uncertainties on the future of the Party. This book will be of key interest to researchers and students in the fields of political studies and contemporary history as well as the interested general reader"--
Keywords: Kinnock, Neil -- 1942-; Labour Party -- Großbritannien; Labour Party (Great Britain) / History / 20th century; Kinnock, Neil Gordon / 1942-; Great Britain / Politics and government / History / 20th century; Labour Party (Great Britain); Politics and government; Great Britain; 1900-1999; History; Aufsatzsammlung